Bilinguality and Socioeconomic Status (SES): Approaching Non-Singular Factor to a Child’s Cognitive Development - Risa Rumentha Simanjuntak (Lingua Cultura, 2013)
Article attempted to argue that bilingualism have positive contributions toward a child’s cognitive development. By applying library research the discussion is focused on the contribution bilingualism had in mitigating socioeconomic detrimental effects on a child’s learning. Article started with discussing aspects of cognition, especially those shown through speech productions, of a bilingual child, then moving forward to discuss previous findings and arguments from the research pertaining to the issue of low socioeconomic status (henceforth SES) and cognition. Finally, the discussion concluded that bilingualism should be discussed as a complex system of learning and not as separate strands of a child’s learning.